2012
DOI: 10.1111/geb.12014
|View full text |Cite
|
Sign up to set email alerts
|

Elevational Rapoport's rule is not pervasive on mountains

Abstract: Aim Elevational Rapoport's rule, proposed in 1992 by Stevens, predicts that species ranges on mountains become larger in elevational extent with increasing elevation. Here we test this prediction using 160 datasets of range size measured by maximum elevational extents for bats, birds, frogs, non‐volant small mammals, reptiles, and salamanders from mountains around the globe. Location Mountains distributed globally and spanning 36.5° S to 48.2° N. Methods We compare three methods: (1) the Stevens method, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 77 publications
(230 reference statements)
5
75
2
1
Order By: Relevance
“…In freshwater systems, a few studies on larger organisms such as fish and insects have tested for its general validity with contradicting results (Fu et al, 2004;Beketov, 2009). Overall, our results agree with the review by McCain & Knight (2013), concluding that Rapoport's elevational rule does not offer 'a consistently predictive pattern' for understanding trends in altitudinal range size. This may reflect relatively short climatic gradients in the study region in relation to physiological tolerances of diatoms.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In freshwater systems, a few studies on larger organisms such as fish and insects have tested for its general validity with contradicting results (Fu et al, 2004;Beketov, 2009). Overall, our results agree with the review by McCain & Knight (2013), concluding that Rapoport's elevational rule does not offer 'a consistently predictive pattern' for understanding trends in altitudinal range size. This may reflect relatively short climatic gradients in the study region in relation to physiological tolerances of diatoms.…”
Section: Discussionsupporting
confidence: 60%
“…mountain base and top) and overlap more towards the centre of the domain. Many higher taxa such as plants or vertebrates seem not to comply with Rapoport's elevational rule (McCain & Knight, 2013), but no test of this rule has been carried out for microbial taxa. Historical hypotheses suggest in turn that species distributions reflect the influence of some historical imprints such as evolutionary constraints on species ranges.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find evidence for a general elevational Rapoport's rule (Stevens, ) in stream organisms, either with Steven's (Stevens, ) or with McCain's methods (McCain and Bracy, ). Our findings, however, are consistent with observations made in a wide range of terrestrial taxonomic groups (reviewed by McCain and Bracy, ), stream biofilm diatoms (Teittinen et al ., ) and some fish studies (Fu et al ., ), suggesting that there is not a consistent positive range size‐elevation relationship. However, Beketov () found that, along a 2500‐m elevational gradient in Russia, mayfly species elevational ranges expanded with the increase in the ranges’ midpoints and that the mean range per elevational band increased with elevation and concurrent decrease in species richness.…”
Section: Discussioncontrasting
confidence: 59%
“…Those species should then have broader fundamental niches, and consequently be capable of persisting across a broader range of climatic conditions along a latitudinal climate gradient. However, many studies on Rapoport's Rule or the CVH do not quantify the gradients in their study areas (e.g., Fu et al 2004, Almeida-Neto et al 2006, McCain and Knight 2013, which is critically relevant to interpretation of results. It is important to clarify that ''climatic variability'' under this definition is the variability in the specific area from which the species originated, not necessarily the absolute variability across the entire current range of the species, which necessarily increases with increasing range size.…”
Section: The Climatic Variability Hypothesismentioning
confidence: 99%
“…Some recent studies have addressed these statistical challenges by using randomization to compare results to appropriate null models (Lyons and Willig 1997, Diniz-Filho and Tôrres 2002, Ribas and Schoereder 2006, Beketov 2009, Davies et al 2011, Morin and Lechowicz 2011, Morin and Lechowicz 2013, by using more advanced grid-cell analyses over a two-dimensional landscape (Smith et al 1994, Meliadou and Troumbis 1997, Ruggiero et al 1998, Ruggiero and Hawkins 2006, Morin and Lechowicz 2011, Luo et al 2011, Whitton et al 2012, Morales-Castilla et al 2013, Morin and Lechowicz 2013 accounting for more complex climate patterns than simple latitudinal gradients, or by using quartile analyses to assess the impact of different groups of range sizes within the data set (e.g., by using only restricted-range species [Amend et al 2013, McCain and Knight 2013, Morin and Lechowicz 2013). However, evidence for Rapoport's Rule remains equivocal.…”
Section: Introductionmentioning
confidence: 99%